The sounds of memory: Troubling the professionalization of knowledge through Black women's memoir and interpretive disability studies. (December 2022) - Cagulada, Elaine; DeWelles, Madeleine
In this article, the authors encourage the consideration of the use of Black women's memoir to inform pre-service early childhood education by exploring Mary Herring Wright's memoir of growing up Black and deaf in the southern USA in Sounds Like Home and bell hooks' memoir of childhood in Bone Black: Memories of Girlhood . In their engagement with Wright and hooks, stories of childhood, longing and memory appear as valid forms of knowing that attend to issues of power, hegemony and social inequity. The authors further demonstrate that the standards of practice promoted within the Ontario College of Early Childhood Educators, particularly 'Standard II: Curriculum and Pedagogy', understand knowledge as valid primarily if based on empirical and developmental ways of knowing. Black women's memoirs and counternarratives, engaged with from an interpretive disability studies perspective, trouble this by suggesting that memories and stories of childhood also serve as valid and important forms of knowledge in pre-service early childhood education training and beyond . How might one encourage and support a disability studies approach to inclusion in pre-service early childhood education settings? How might such an approach help blur the child–adult binary that often appears in pre-service early childhood education, and in almost all the relationships that children have with adults? Melding the creative and the critical, the authors argue that Black women's memoir can deepen our understanding of belonging and love, and therefore is a necessary intervention in educational institutions embedded within a normative order that creates binaries between children and adults.